Can We Teach Environmental Education in English Courses? - Rebecca Rosario O. Bercasio (RIRAI Publisher, 2022)
The preparation of teaching and learning resources in environment education (EE) is important because it supports the attainment of the goals of RA 9512 and addresses the lack of teaching and learning resources in EE (Kimaryo, 2011). Using mixed methods of research, the study aimed to review the English Education curriculum to identify entry points of EE integration using the Department of Environmental and Natural Resources (DENR) EE materials, and to develop and to validate exemplar session plans with EE integration in different English Education courses. Data were gathered using documentary analysis, assessment of the DENR EE materials, and assessment of the proposed session plans using rubric. Results show that the entry points for EE integration is adequate, and that the DENR EE materials are found to be appropriate, relevant, and highly flexible as instructional materials for EE integration in English courses. EE can be integrated in the different parts of the lesson such as the motivation, lesson proper and assessment. The proposed session plans were rated excellent by the jurors, and therefore serve as acceptable and relevant materials for the mainstreaming of EE in the English Education curriculum. Wide dissemination and pilot-testing of the session plans integrating EE are recommended.